(untitled) (INCH : Journal of Infant and Child Healthcare, 2026)
Undernutrition remains a health problem that can affect children’s growth and development. This study aimed to describe the weight gain of undernourished toddlers after receiving Local PMT for 56 days. This study used a descriptive design with a quantitative approach utilizing secondary data. The research sample consisted of 30 undernourished toddlers who received Local PMT, selected using a total sampling technique. Data analysis was conducted univariately. The results showed that the number of male and female toddlers was equal, each accounting for 50% of the sample. Most toddlers did not finish consuming the Local PMT during the 56-day period, totaling 21 toddlers (70%), while 9 toddlers (30%) completed the Local PMT. All toddlers did not experience weight gain in accordance with the standards outlined in the 2025 PMT Technical Guidelines. These outcomes were influenced by compliance with PMT consumption, the toddlers’ health conditions, as well as parenting practices and feeding patterns at home